Development of Diagnostic Assessments for Islamic Religious Education Learning in Junior High Schools in Bandung Regency - Nasrulloh, Ilham; Suresman, Edi; Fahrudin, Fahrudin (Universitas Negeri Padang, 2024)
From the preliminary research data obtained, about 74% had never made diagnostic assessment instruments, and 13% indicated they had made them. Therefore, teachers need tools to understand students' learning needs and abilities. The purpose of this study is to help teachers by developing diagnostic assessment instruments for PAI learning in junior high schools. This research method uses the research and development method (Research And Development) with the ADDIE model in making instrument questions through five stages developed by Dick and Carry. Data was collected by testing 383 students from 4 junior high schools in Bandung Regency. This data collection tool uses Google Forms. Data analysis in this study used descriptive statistics and item analysis by looking at Validity, Reliability. This shows that it is reliable and valid. The results of the difficulty level analysis show that the instrument has an easy difficulty level of 2.50%, medium 77.50% and difficult 20.00%. The results of the analysis of the differential power 38 items have